MODEL INTEGRATIF KULIAH LAPANGAN DAN CASE-BASED LEARNING DALAM PENGEMBANGAN KOMPETENSI MAHASISWA TEKNIK ELEKTRO - Muljono, Agung Budi; Adnyani, Ida Ayu Sri; Harjian, Muhammad Rivaldi; Nababan, Sabar (Universitas Mataram, 2025)
This integrative learning activity aims to develop the competencies of Electrical Engineering students through a learning model that combines Field Study and Case-Based Learning (CBL) in the Substation Technology course. Technical competence in the field of substations requires a strong theoretical foundation as well as practical skills in solving real-world problems in the field. The activity was carried out through visits to substations owned by industry partners and the development and resolution of case studies based on actual field situations. The final evaluation results show that this model had a significant impact on academic achievement, with 60.2% of students achieving excellent grades, 34.4% good, and 5.4% satisfactory. In addition, the questionnaire analysis, consisting of 10 indicators, revealed a high level of satisfaction, with 55.357% of respondents strongly agreeing and 39.285% agreeing with the effectiveness of this learning model. This model has proven to be effective as a learning strategy for strengthening student competencies while also serving as a tangible contribution of higher education in fostering synergy with society and industry.